EVALUASI PROGRAM SIMPAN PINJAM BADAN USAHA MILIK DESA KARANGSEMBUNG KECAMATAN KARANGSEMBUNG KABUPATEN CIREBON - Utami, Widya Dwi; Kusmarianto, Cicuk (PARADIGMA: Jurnal Ilmu Administrasi, 2023)
This research aims to find out and evaluate the management of the BUMDes Makmur Sejahtera savings and loan program in Karangsembung Village, Karangsembung District, Cirebon Regency, why it is not yet optimal. The method used is descriptive qualitative. Data sources were obtained from observation, interviews and documentation. The technique for determining informants is purposive sampling. Data analysis techniques go through the stages of data collection, data reduction, data presentation and drawing conclusions. The research results show that the BUMDes Makmur Sejahtera savings and loan program has been implemented quite well and has received a positive response from the community. The problems found were limited capital, inadequate infrastructure, problems with bad credit and profits from business results were still very limited.Keyword: Program Evaluation; Savings and Loans; BUMDes.